"Garnet" Lherzolites in the Purang Ophiolite, Tibet: Evidence for Exhumation of Deep Oceanic Lithospheric Mantle. Issue 1 (17th January 2020) - Gong, Xiao‐Han; Shi, Ren‐Deng; Xu, Ji‐Feng; Huang, Qi‐Shuai; Huang, Xiao‐Xiao; Su, Ben‐Xun
Abstract: Ophiolites commonly sample the uppermost parts (15–20 km) of fossil oceanic lithosphere. However, in recent years, the documentation of diamonds, super‐reducing (e.g., SiC), and other "unusual" minerals from several ophiolitic peridotites and chromitites (e.g., Tibet and the Polar Urals) has caused debate concerning their origin (i.e., deep vs. shallower upper mantle). Here we report on symplectite‐bearing lherzolites from the Purang ophiolite in Tibet, which preserve the first compelling evidence of garnet‐facies protoliths. These lherzolites were previously formed and stabilized at a depth of 85–100 km, which is much deeper than generally suggested and approaches the depth ( 120 km) required for stabilizing the diamonds. Combining with other key observations, we suggest the Purang garnet‐bearing peridotites may represent mixtures of oceanic lithosphere domains with diverse origins; they were rapidly exhumed at a variety of mantle depths within a subduction channel associated with oceanic slab retreat. Plain Language Summary: Ophiolites are remnants of fossil ocean basins that have been emplaced on land and usually sample the upper 15–20 km of oceanic lithosphere. However, the discovery of diamonds, super‐reducing, and other "unusual" minerals from several ophiolitic peridotites suggests that these peridotites might originate in the deep upper mantle (>300 km), challenging conventional models of ophiolite formation. In this study, we show that symplectite‐bearing lherzolites from the Purang diamond‐bearing ophiolite (Tibet) were originally garnet‐bearing peridotites, with a previous equilibration depth of 85–100 km. Our results suggest that the Purang peridotites may represent mixtures of oceanic lithosphere domains with different nature and origins, which were exhumed and mixed within an oceanic subduction channel associated with slab retreat. Key Points: Symplectite‐bearing lherzolites from a Tibetan diamond‐bearing ophiolite formed from garnet peridotite protoliths These lherzolites were previously formed and stabilized at a depth of 85‐100 km, much deeper than previously suggested An oceanic subduction channel model is suggested for exhumation of some of the Tibetan diamond‐bearing peridotites